Regionalization of Non-State Security Agencies in Southwest Nigeria: Prospects and Challenges of “Amotekun” - Odewale , Ayotunde David; Lamidi , Kazeem Oyedele (European Scientific Journal, ESJ, 2020)
The necessity of policing by all actors, both the state and non-state, becomes more expedient in Nigeria societies characterized by diver’s insecurities vices range from book-haram insurgency, kidnapping, banditry, armed robbery, herdsmen/ farmer clash, and ritual killing. The process of localizing security architecture is essential in Nigeria federation, so as tackled this menace of insecurities that have been threating the unity of Nigeria nation. This paper examines the modalities and theoretical insights of the operation Amotekun initiative in the Southwest Nigeria with a view to providing information on the prospects and challenges of the regional security network. Data was garnered basically from secondary sources. It is assumed that the criminality that have pervaded southwest Nigeria could be reduced to minimal, if the initiative is well managed, and in extension, to the entire federation. The paper identified some challenges that may confront the initiative, which range from; unnecessary suspicion among the nations in Nigeria federation, conflict with other statutory security agencies, and using the initiative to settle personal discord among others. It recommends the need for legal framework from each state of the region for its establishment, operations, and finance and appropriate synergy among all the tiers of government and agencies of government in security sector so as to achieve the ultimate goal of securing lives and properties. The paper concluded that operation Amotekun should be nurtured because there is nothing too big in securing the lives and properties of the citizen, which is the primary function of any government.